A tertiary experience of ileal–ureter substitution: Contemporary indications and outcomes. (3rd May 2016) - Gomez-Gomez, Enrique; Malde, Sachin; Spilotros, Marco; Shah, P. J.; J. Greenwell, Tamsin; Ockrim, Jeremy L.
Abstract: Objective. Complex ureteric stricture disease in contemporary practice is typically related to prior pelvic surgery, radiotherapy, or complicated, repeated retrograde stone surgery, although outcomes in this group have not been well studied. The aim of this study was to report medium-term outcomes with ileal–ureter substitution for complex ureteric stricture disease. Materials and methods. All patients who had undergone ureteric reconstructive surgery using small bowel over a 5 year period between 2010 and 2015 were identiﬁed from the theatre database and their case notes reviewed. Data were collected on aetiology of ureteric stricture, prior surgery or radiotherapy, baseline renal function and comorbidity. Postoperative complications were recorded using the Clavien–Dindo classification, and overall outcome and need for further intervention were documented. Results . Nine patients underwent ileal–ureter substitution for complex ureteric stricture disease over this period, with four having bilateral ileal interpositions. Median age was 48 years (38–62 years) with a median follow-up of 17 months (1–40 months). Simple untailored ileal segments and refluxing anastomoses were used in all cases. One case of anastomotic leak and restricture required reintervention, but all others had favourable outcomes with no stricture and no requirement for further intervention. Two patients reported recurrent cystitis following surgery but there was no deterioration in renal function in any patient, with no metabolic complications reported. Conclusion . Ileal–ureter substitution surgery is a valuable option for selected patients with complex, difficult-to-treat ureteric defects that cannot be bridged by other methods. Simple onlay techniques do not seem to affect renal or metabolic function. Avoiding the extra complexity of tailored and tunnelled anastomoses may reduce the potential morbidity and reintervention rate in patients with challenging surgical fields.